Study on hot deformation behavior of 9Cr18Mo stainles bearing steel - ZHANG Yu; WANG Jianguo; LIU Dong; LIANG Zhirui; ZHAO Jiahang (Xibei Gongye Daxue Xuebao)
The microstructure evolution and hot deformation behavior of 9Cr18Mo stainless bearing steel were studied with the hot compression test at the temperature ranging from 1 223 to 1 423 and strain rates from 0.01 to 10 s-1. The results indicate that the 9Cr18Mo stainless steel shows strong positive strain rate sensitivity and negative temperature sensitivity. The softening mechanism is dynamic recrystallization and dynamic recovery mechanism. A constitutive equation with the strain compensation considered was developed and the prediction value is in good agreement with the experimental value. The processing map of 9Cr18Mo stainless steel was established with the Murty criteria. Combined with microstructure analysis, the optimal hot processing parameter range is between 1 050 ℃ and 1 120 ℃ and the strain rate is between 0.1 and 1 s-1. The composition distribution of the microstructure of 9Cr18Mo stainless steel was analyzed with the EDS. In combination with the calculation results of the JMAPTPRO software, it was determined that the coarse banded carbides were not dissolved in the matrix at high temperature were composed of M7C3 carbide and M23C6 carbide.